Методи оцінки конкурентоспроможності будівельних підприємств - Сич, Ольга Сергіївна (НТУ "ХПІ", 2015)
Проаналізовано основні підходи до оцінки конкурентоспроможності підприємств, виявлено недоліки існуючих підходів для оцінки рівня конкурентоспроможності будівельного підприємства, пропонується авторська методика оцінки конкурентоспроможності будівельного підприємства.

There have been analyzed the main approaches to assessing the competitiveness of enterprises, identified deficiencies of existing approaches to assess the level of competitiveness of the building enterprise, the author proposed method for assessing the competitiveness of the building enterprise.
Methods for assessing the competitiveness of construction companies
Keywords: показники конкурентоспроможності; КСП; организації-конкуренти; комплексна оцінка; competitiveness of enterprises; competitiveness indicator